Associations between styloid process sheath CT sizes and age, body weight, and breed in horses. Issue 4 (21st February 2022) - Whitty, Justin A.; Miller, Allison V.; Miller, Andrew D.; Carney, Patrick C.; Scrivani, Peter V.
Abstract: The styloid process sheath (SPS) is a part of the tympanic temporal bone and an incomplete bony sleeve surrounding the styloid process, tympanohyoid cartilage, and dorsal part of the stylohyoid bone. In horses undergoing head CT, we observed a range of SPS sizes and questioned whether differences were early features of temporohyoid osteoarthropathy (THO) or normal anatomic variations associated with age, body weight, sex, or breed. We hypothesized that SPS sizes were positively correlated with age and body weight, but not with sex or breed. Using a convenience population of horses that underwent head CT at our institution (2008–2017), regardless of THO status, we investigated these hypotheses in a retrospective cross‐sectional study. The sample comprised 102 horses. The median SPS height was larger medially (4.3 mm) than laterally (2.4 mm) and the median width was 11.1 mm: no difference was detected between sides. Geldings had a significantly larger median SPS width (11.6 mm) than stallions (8.7 mm; P  < 0.05) and mares (10.0 mm; P  < 0.05). No association was detected between SPS sizes and body weight and breed. Univariate and multivariate analyses initially found significant associations between SPS heights and age. Secondary analyses performed following removal of outliers and horses <2‐years old found similar but less pronounced results (annual increase in SPS heights decreased from 3.2‐3.8% to 0.9‐2.6%). Most associations were insignificant when investigated by age group, but the annual rate of increased size might be faster in older horses. Excessive SPS enlargement was theorized as an essential component of THO.